The adolescent's experience of cancer: An integrative literature review. Issue 4 (August 2019) - Drew, Donna; Kable, Ashley; van der Riet, Pamela
Abstract: Aim: This integrative review appraises the literature that explores the experiences of the adolescent diagnosed with cancer. Background: The cancer experience has an impact on the way the adolescent lives their life, their future hopes dreams and fears, their health and wellbeing. Healthcare professionals require an understanding of what the adolescent experiences after a diagnosis of cancer and during the treatment experience to be able to provide optimal age appropriate care. Methods: The review was conducted following Whittemore and Knafl's (2005) framework. A comprehensive search using the following four databases, CINAHL, MEDLINE, PyschINFO, Embase was undertaken for the period of 2005–2016. Google scholar, healthcare policies and guidelines reference lists were also searched. Screening and appraisal of 911 articles resulted in 22 articles being included in this review. Findings: Three themes were identified: 'Losing what I know - this is what makes me different', 'Communication and information sharing - the need to know', and 'The importance of friends, peers and relationships'. Conclusion: This review reports that healthcare providers should be aware of the changing self-perceptions the adolescent experiences throughout the cancer journey. Accessing this information will enable healthcare providers to determine more appropriate care when these adolescents are feeling most vulnerable. The review identified there is limited information about the experience of the younger adolescent (11–15 years) with cancer. Future research may benefit from focusing on the stage of development of the adolescent with cancer.